Study on preparation method and carbon fixation performance of supercritical CO2-foamed concrete - Ta, Xupeng; Zhang, Yuan; Wan, Zhijun; Li, Jianwei (Construction & building materials, 2025)
Utilizing supercritical CO2 phase-transition foaming technology to fabricate foam concrete with enhanced carbon sequestration represents an attractive approach. This study designed and developed an experimental system for supercritical CO2-foamed concrete (sCFC), through which a series of systematic experiments were conducted. The investigation focused on the preparation methodology of sCFC, while systematically examining the influence mechanisms of supercritical CO2 on the mechanical properties, pore structure characteristics, and carbon sequestration capacity of the resultant foam concrete. The experimental results revealed that sCFC preparation requires a dynamic control of the temperature and pressure conditions, considering the characteristics of Portland cement and its reaction with CO2 mineralization. The 28-d compressive strength of sCFC was determined to be 4.90–5.79 MPa. Increasing the pressure and pressure holding time further promoted the cement hydration reaction and enhanced the strength of the sCFC samples. The porosity of sCFC was determined to be 47.87–89.79 %, and it was affected by the diffusion–dissolution–reaction behavior of CO2 in the supercritical CO2–concrete system. The carbon fixation rate per ton of sCFC skeleton was 6.32–10.36 %, indicating significant carbon fixation potential. sCFC can be used as a low-carbon functional material for mining and thus contribute to reducing the source carbon of coal and electricity integration base. •The method of preparing foam concrete by supercritical CO2 phase change foaming is invented.•The growth of CO2 bubbles is affected by the mineralization reaction.•Carbon fixation rate of supercritical CO2-foamed concrete skeleton is 6.32–10.36 %.